2010
DOI: 10.1002/jbt.20379
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol‐induced redox imbalance in rat kidneys

Abstract: This study reports the effects of long-term ethanol consumption on kidney redox status, in terms of enzymatic mechanisms involved in regulating the cytosolic [NADH]/[NAD(+) ] balance. Wistar rats were treated with ethanol (2 g/kg body weight/24 h) via intragastric intubation for 10 and 30 weeks, respectively. Ethanol administration induced an enhancement of alcohol dehydrogenase activities and affected the capacity of the kidney to prevent NADH accumulation in the cytosol. After 10 weeks, the excess of NADH wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Increased level of creatinine signifies ethanol‐induced alteration in glomerulus filtration rate that might lead to a reduced rate of renal creatinine clearance as is observed by Ojeda, Barrero, Nogales, Murillo, and Carreras (2012). According to Nechifor and Dinu, (2011), the deleterious impacts of ethanol on kidney are due to the increased activities of alcohol dehydrogenase, lactate dehydrogenase, and malate dehydrogenase. Recently, Shanmugam, Mallikarjuna, and Reddy (2011) have reported that ethanol‐induced oxidative stress causes a significant decrease in the levels of antioxidant enzyme viz, catalase, and superoxide‐dismutase activities along with an increase in MDA in the kidney of the rats, which is in accordance to our observation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased level of creatinine signifies ethanol‐induced alteration in glomerulus filtration rate that might lead to a reduced rate of renal creatinine clearance as is observed by Ojeda, Barrero, Nogales, Murillo, and Carreras (2012). According to Nechifor and Dinu, (2011), the deleterious impacts of ethanol on kidney are due to the increased activities of alcohol dehydrogenase, lactate dehydrogenase, and malate dehydrogenase. Recently, Shanmugam, Mallikarjuna, and Reddy (2011) have reported that ethanol‐induced oxidative stress causes a significant decrease in the levels of antioxidant enzyme viz, catalase, and superoxide‐dismutase activities along with an increase in MDA in the kidney of the rats, which is in accordance to our observation.…”
Section: Discussionmentioning
confidence: 99%
“…According to Nechifor and Dinu, (2011), the deleterious impacts of ethanol on kidney are due to the increased activities of alcohol dehydrogenase, lactate dehydrogenase, and malate dehydrogenase.…”
Section: Discussionmentioning
confidence: 99%